RANCANG BANGUN SISTEM TANGGAP DARURAT MENGGUNAKAN PANIC BUTTON TERINTEGRASI - Saputra, Faisal Mahendra; Firdaus, Firdaus; Dahlan, Andi Ahmad (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Security is an important aspect of human life, especially in residential environments that require fast and easily accessible emergency communication systems. This research aims to build an emergency response system using ESP32-based panic buttons that can operate without internet, allowing all nodes to send and receive emergency signals simultaneously, and supporting easy addition of new nodes. The research method uses ESP32 microcontrollers with ESP-NOW communication protocol to form a Peer-to-peer (P2P) mesh network. Each node can function as both sender and receiver of signals simultaneously through a mesh topology that does not depend on centralized infrastructure. Test results show that the system can operate with an optimal range of 150 meters and a maximum of 200 meters under unobstructed conditions, while under obstructed conditions the optimal range becomes 15 meters. Peer-to-peer testing proves the system's capability in maintaining communication through intermediate nodes when direct connections are lost. Systems with different systemIDs successfully create effective network isolation. Adding new nodes only requires loading the same program code without additional configuration. This system proves effective as a simple, efficient, and responsive local-scale emergency communication solution for implementation in residential environments or public facilities.